2014
DOI: 10.1136/bcr-2014-203805
|View full text |Cite
|
Sign up to set email alerts
|

Non-operative management of a grade IV pancreatic injury

Abstract: Isolated pancreatic transection with ductal disruption in blunt abdominal trauma is extremely rare. We report the case of a 14-year-old boy who suffered pancreatic transection at the junction of body and head of the pancreas; yet remarkably recovered after initial conservative management. He was periodically examined clinically and underwent regular abdominal ultrasonography. Nearly 6 months later, endoscopic retrograde cholangiopancreatography with pancreatic duct stenting, pancreatic sphincterotomy and cysto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…The ERCP may play a role in duodeno-pancreatic trauma in order to avoid late-diagnosis and/or treatment both in adult and pediatric patients [10, 15, 4143, 48–52, 58–60, 6264, 67, 68, 70, 7678, 90, 97, 101, 127149]. It is an invasive procedure with 3–14% risk of post-procedure pancreatitis and 0.2–1% mortality rate [6, 10, 11, 40, 41, 45, 49, 5153, 58, 6164, 67, 68, 70–72, 75, 77, 78, 97, 128, 130, 133, 134, 137140, 142, 144, 146, 148157]. Moreover, in suspected duodenal perforations, the ERCP is not recommended.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ERCP may play a role in duodeno-pancreatic trauma in order to avoid late-diagnosis and/or treatment both in adult and pediatric patients [10, 15, 4143, 48–52, 58–60, 6264, 67, 68, 70, 7678, 90, 97, 101, 127149]. It is an invasive procedure with 3–14% risk of post-procedure pancreatitis and 0.2–1% mortality rate [6, 10, 11, 40, 41, 45, 49, 5153, 58, 6164, 67, 68, 70–72, 75, 77, 78, 97, 128, 130, 133, 134, 137140, 142, 144, 146, 148157]. Moreover, in suspected duodenal perforations, the ERCP is not recommended.…”
Section: Methodsmentioning
confidence: 99%
“…CT-scan is usually the first-line imaging tool in the assessment of late complications of pancreatic trauma and very useful in driving management [39, 61, 71, 72, 76, 96, 135, 145, 233, 247, 248]. MRI is a reliable alternative to CT-scan in children and pregnant women [40, 45, 52, 97, 249, 250].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the method cannot be easily selected, the probability of postoperative complications due to pancreatic resection or anastomosis in a pancreatic injury is as high as 40% [10]. Recently, some reports have suggested that NOM using endoscopic pancreatic duct stenting could be a useful and safe option in selected patients [11]. In this case, we selected PD because we suspected a coexisting duodenal injury.…”
Section: Discussionmentioning
confidence: 95%
“…Миниинвазивное лечение в ранние сроки после травмы, если оно возможно, улучшает результаты консервативной терапии и уменьшает частоту специфических осложнений [60,108,109,110], к которым относятся травматический панкреатит [12,20,25,26], парапанкреатическая киста [1,56,66,11,111], наружный панкреатический свищ [1,112,113], стеноз панкреатического протока [114], внутрибрюшной абсцесс [30,115]. Отдаленные результаты эндоскопического лечения пока не всегда удовлетворительные [114].…”
Section: закрытая травма живота повреждения поджелудочной железы чаunclassified